Dynamics and trophic role of zooplankton community in the Matang mangrove estuaries and adjacent coastal waters (Peninsular Malaysia), with special emphasis on copepods / Chew Li Lee - Chew, Li Lee (2012)
Dynamics and trophic role of zooplankton community were studied in the Matang mangrove estuaries and adjacent coastal waters, Malaysia. Monthly zooplankton samples collected from May 2002 to October 2003 at five stations located from the upper estuary (7 km upstream) to 16 km offshore showed highest biomass and abundance of zooplankton at nearshore waters. Both standing stocks decreased towards upstream and offshore waters. Copepods (62% of total zooplankton abundance) dominated the zooplankton, followed by larvae of cirripede (18%) and polychaete (4%). Copepod abundance was higher during the wetter northeast (NE) monsoon and inter-monsoon (IN) period as compared to the drier southwest (SW) monsoon. Multivariate analyses revealed that the structure of the zooplankton community in the upper reaches of Matang was distinctively different from that of the adjacent coastal waters which was attributed to the spatial and temporal variations in environmental conditions. Salinity, food availability and quality, and predation were the main factors influencing zooplankton abundance and composition. Twenty-four hour samplings of surface and bottom zooplankton in the lower estuary, encompassing four consecutive lunar phases in July 2003 (dry period) and November 2003 (wet period), showed that the adults of four dominant copepod species (Acartia spinicauda, Parvocalanus crassirostris, Bestiolina similis and Oithona simplex) and mysids were significantly more abundant during night than day. This diel pattern was less obvious for meroplanktonic larvae of cirripedes, brachyurans and polychaetes, although they were consistently more abundant during ebb than flood tide. More cirripede and polychaete larvae were sampled during neap tide compared to spring tide, especially during the dry period. The neap tide zooplankton community during the wet period was dominated by the estuarine copepod A. spinicauda. The demersal copepod Pseudodiaptomus annandalei occurred in high numbers during the wet spring tide period. P. crassirostris and brachyuran zoeae were about equally abundant during the dry and wet period, although consistently more abundant during spring than neap tide. The implications of short-term zooplankton variability, the potential mechanisms of zooplankton response to short-term environmental variations and the significance of their adaptive mechanisms were evaluated. The trophic role of zooplankton in the mangrove and adjacent coastal water food web was elucidated. Stomach contents of 2183 juvenile fish belonging to 26 species revealed significant consumption of zooplankton food. Copepods were the most important zooplankton food consumed by fish followed by Acetes, mysids, cirripede larvae and amphipods. The copepod species, P. annandalei, was the most important species, being consumed by most small-sized fishes. The dominant copepods Acartia and P. crassirostris were mainly exploited by ambassids and engraulids. The hyperbenthic shrimps, Acetes spp. and mysids, were fed by various economically-important fish species. Stable isotope analysis indicated high dependency of zooplankton on phytoplankton rather than mangrove carbon in the estuary, with assimilation of benthic microalgae in nearshore waters. The range of δ15N values indicated at least four trophic levels, with zooplankton at the second and third trophic level.